PREVALENCE AND CONTROL OF HYPERTENSION WITH THE USE OF AMBULATORY BLOOD PRESSURE RECORDING IN HEMODIALYSIS PATIENTS. (June 2018) - Loutradis, C.; Karpetas, A.; Papadopoulou, E.; Piperidou, A.; Bikos, A.; Raptis, V.; Tzanis, G.; Syrganis, C.; Stamatiadis, G.; Liakopoulos, V.; Papagianni, A.; Zebekakis, P.; et al.
Abstract : Objective: To date, there is no commonly accepted definition for hypertension in patients with chronic kidney disease undergoing hemodialysis. A recent expert consensus suggests hypertension in dialysis to be defined based on ambulatory blood pressure monitoring (ABPM). The aim of this study is to evaluate the prevalence and control of hypertension using ABPM in a large hemodialysis population according to the latest definitions. Design and method: A total of 160 hemodialysis patients underwent 48-hour ABPM, during a regular hemodialysis session and the subsequent interdialytic interval. Hypertension was defined as (i) pre-hemodialysis BP >  = 140/90 mmHg or use of antihypertensive agents (ii) ambulatory BP >  = 130/80 mmHg (over 44-hours or over the second 24hour period) or use of antihypertensive agents. Phenotypes of hypertension control were defined as: 1) concordant control (pre-hemodialysis BP < 140/90 mmHg and ambulatory-BP < 130/80 mmHg), 2) concordant lack of control (pre-hemodialysis BP >  = 140/90 mmHg and ambulatory-BP >  = 130/80 mmHg), 3) "white coat" phenomenon (pre-hemodialysis BP >  = 140/90 mmHg and ambulatory-BP < 130/80 mmHg) and 4) masked hypertension (pre-hemodialysis BP < 140/90 mmHg and ambulatory-BP >  = 130/80 mmHg). Results: Based on pre-hemodialysis BP levels, the prevalence of hypertension was 91.3% Based on the ABPM covering the total 44-hour or the 2nd 24-hour interdialytic period, the prevalence was 88.8%. The proportion of hypertensive patients receiving treatment was 124 (84, 9%). With the use of pre-hemodialysis BP and ABPM during 44-hours, 12 (10.1%) of hypertensive patients had concordant BP control, 87 (58.8%) of patients had lack of control, 29 (19.6%) had a white-coat phenomenon, and 17 (11.5) masked hypertension, respectively. In multivariate logistic regression analysis, only use of antihypertensive agents was independently associated with increased odds for lack of control (reverse causation). Conclusions: Hypertension prevalence in hemodialysis patients is overwhelmingly high. The rates of control rates are different when calculated from office and ambulatory BP recordings. In the population studied, almost one out of three patients had white-coat or masked hypertension.